PT. HM. Sampoerna Tbk and Its Strategies Becoming a Market Leader Since 2006 - Diin Fitri Ande (Jurnal Ekonomika dan Manajemen, 2018)
PT.HM. Sampoerna Tbk has been a market leader since 2006 in cigarettes industry in Indonesia despite the challenges has been faced by the industry such tax exercise, health campaign, and illicit trade. This study elaborates the strategies that have been taken by Sampoerna in order for the company maintain its position as a market leader. This a qualitative research based on literature review using industry analysis and study on corporate, business and functional level strategy. It is found that Sampoerna able to maintain its performance due its ability to provide the commitment to deliver good quality to the consumers and to innovate in its products and processes. In business level strategy, Sampoerna pursues both cost leadership and differentiation strategy.  In addition, Sampoerna functional strategies in Makerting and Human Resources are worth to appreciate as they have significant contribution to Sampoerna’s success